Prevalence of Echinococcus spp. Infection Using Coproantigen ELISA among Canids of Moghan Plain, Iran - M Zare-Bidaki; I Mobedi; SR Naddaf; EB Kia; M Mahmoudi; N Piazak; H Nekouie; S Sadeghieh Ahari; Sh Habibzadeh; M Siavashi (Tehran University of Medical Sciences, 2009)
"nBackground: Echinococcosis is one of the most important helminthic zoonotic diseases in Iran. Intestinal Scraping Technique (IST), the traditional method for diagnosis of the infection in definitive hosts, has many disadvantages including low susceptibility and being expensive, hazardous and laborious. Detection of coproantigens in fecal samples by enzyme-linked immunosorbent assay (CA-ELISA) is known as a useful tool for intravital mass-screening of definitive host populations. This study was performed to determine the prevalence of Echinococcus spp. infection among canids in Moghan plain, the only area in Iran known to be endemic for E. multilocularis."nMethods: One hundred thirty eight fecal samples were collected from red foxes and domestic dogs in three counties of Moghan plain namely Pars Abad, Bileh Savar and Germi. The samples were examined using an ELISA, designed for the detection of Echinococcus-specific coproantigen and the formalin-ether concentration method as well."nResults: Totally, out of 138 fecal samples, 27 (21.6%) turned positive for Echinococcus. Coproantigen was detected in 16.7% and 27.1% of red foxes and domestic dogs, respectively. Formalin-ether concentration method revealed that 43 (31.2%) of samples harbored at least one parasitic helminth, but Taenia eggs were detected only in 3 fecal samples. Since coproantigen presence reflects current intestinal infection with adult worms, CA-ELISA can be regarded as one of the most useful immunological tools for diagnosis of Echinococcus infection. Besides, the high susceptibility, low cost and rapidity